Pelaksanaan Pembelajaran Tematik di Sekolah Dasar Islam Terpadu Izzuddin Palembang - Hidayat Hidayat (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2018)
This research is entitled the implementation of thematic learning in Integrated Islamic Elementary School Izzuddin Palembang. Thematic learning is given with the intention of unifying curriculum content in intact units or units and making learning more integrated, meaningful and easily understood by elementary school students. This study aims to determine the implementation and inhibiting factors and support for thematic learning at SD IT Izzzuddin Palembang. This study uses a qualitative descriptive approach, namely explaining what it is, with data collection tools, documentation, observation, interviews. This research can be concluded first, the implementation of thematic learning in SD IT has been implemented by some teachers, but it has not been optimal as expected, because some teachers who teach in class II do not understand in a comprehensive manner about the implementation of thematic learning. In addition, there are also teachers who have not implemented thematic learning, due to delays in designing thematic learning, there are even teachers who do not make plans for implementing thematic learning. Second, the supporting factors in the implementation of thematic learning include learning resources, learning media, teachers, students, environment, facilities and infrastructure, student comfort. The inhibiting factor for the implementation of thematic learning is the difficulty of the teacher in dealing with students who cannot read, when in making lesson plans (RPP), the teacher must gather, face noisy students when the learning process takes place, adjusting the theme of the lesson with the students